2023
DOI: 10.1021/acsenergylett.3c00052
|View full text |Cite
|
Sign up to set email alerts
|

Weak Solvent–Solvent Interaction Enables High Stability of Battery Electrolyte

Abstract: Electrolytes play an important role in transporting metal ions (e.g., Li+) in metal ion batteries, while understanding the relationship between the electrolyte properties and behaviors is still challenging. Herein, we detect the existence of weak solvent–solvent interactions in electrolytes by nuclear magnetic resonance (NMR), particularly discovering that such interactions have a significant function of stabilizing the electrolytes, which has never been reported before. As a paradigm, we renovated the underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…eNMR can measure the velocities of all four species under an applied one-dimensional electric field across an electrolyte of uniform composition. [28][29][30][31] The velocities of the cation, anion, and both solvents, can be distinguished using 7 Li, 19 F, and 1 H NMR measurements; the 1 H NMR peaks of EC and EMC are well separated. The eNMR cell employed herein consists of a 5 mm NMR tube with platinum (i.e., blocking) electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…eNMR can measure the velocities of all four species under an applied one-dimensional electric field across an electrolyte of uniform composition. [28][29][30][31] The velocities of the cation, anion, and both solvents, can be distinguished using 7 Li, 19 F, and 1 H NMR measurements; the 1 H NMR peaks of EC and EMC are well separated. The eNMR cell employed herein consists of a 5 mm NMR tube with platinum (i.e., blocking) electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work also showed that manipulation of solvent-solvent interactions helps regulate the solvation structure and stabilize the electrolyte. [6][7][8] In an important publication, Doyle and Newman modeled ion transport in lithium-ion batteries based on concentrated solution theory. 9 While this theory is general and can be extended to include any number of components, the electrolyte was approximated as a binary electrolyte comprising two ionic species and one solvent species.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ming et al , proposed a new opinion that Li + ion solvation structure plays a more dominant role than SEI itself in the electrode stability, which is caused by the interplay of the electrolyte components including anions, solvents, and additives. Recently, they demonstrated that tuning the Li + solvation structure according to solvent–solvent interaction and dipole–dipole interaction in the electrolyte would enhance the battery performance. Sun et al also present a new interfacial model to uncover how the electrolyte components play their roles in the battery, further ensuring the stability of the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The components of the electrolytes for commercialized LIBs have been well-recognized, , which are made up of lithium salts (lithium hexafluorophosphate (LiPF 6 )), ethylene carbonate (ethylene carbonate (EC)), linear carbonate ester (ethyl methyl carbonate (EMC), dimethyl carbonate, diethyl carbonate, etc.). Many efforts have been made to investigate the solvation structure in LIBs due to their importance in electrolytes both through experimental and theoretical methods. , However, it is not trivial to distinguish the complex patterns of various peaks in spectrum by experiments, usually requiring sophisticated design to obtain the detailed microstructure, particularly in multicomponent electrolytes. In contrast, molecular dynamics (MD) simulation is inherently based on the information at the atomistic scale, becoming a powerful tool to obtain the detailed solvation structure directly to reveal the microcosmic mechanism, which has been demonstrated in recent studies. ,, For example, Borodin et al , performed MD simulations to investigate the solvation structure in the mixed electrolytes of LiPF 6 /EC/DMC).…”
Section: Introductionmentioning
confidence: 99%
“…2023, 13, 2300443 can enter the solvation shell easily and influence the coordination state of Li + in the fluorinated electrolyte. More information about the electrolyte structure can be acquired by nuclear magnetic resonance (NMR) measurements, [22] particularly for the role of PFPN. The carbonyl 17 O-NMR of different electrolytes and co-solvents (i.e., a pure solvent mixture) sitting between 200 and 275 ppm were analyzed to study the coordination ability (Figure 2d).…”
mentioning
confidence: 99%